2021
DOI: 10.1109/ojcs.2021.3100870
|View full text |Cite
|
Sign up to set email alerts
|

Joint Computation Offloading, Channel Access and Scheduling Optimization in UAV Swarms: A Game-Theoretic Learning Approach

Abstract: Coalition-based unmanned aerial vehicle (UAV) swarms have been widely used in urgent missions. To fasten the completion, mobile edge computing (MEC) has been introduced into UAV networks where coalition leaders act as servers to help members with data computing. This paper investigates a relative delay optimization in MEC-assisted UAV swarms. Considering that the scheduling methods have great impact on the delay, some theoretical analysis are made and a scheduling method based on shortest effective job first (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…(1) In Step 1, the selection of a UAV heads is implemented by contention mechanism. 47 The complexity is OðC1Þ, where C1 is a small constant 37 and is affected by the number of UAV heads. (2) In Step 2, the selected UAV head h q computes the utility of all possible positions in the strategy space and finds the optimal position deployment with computational complexity OðC2Þ, where C2 is constant affected by the number of available positions in the UAV head's strategy space and the Equation ( 14).…”
Section: Algorithm Complexity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(1) In Step 1, the selection of a UAV heads is implemented by contention mechanism. 47 The complexity is OðC1Þ, where C1 is a small constant 37 and is affected by the number of UAV heads. (2) In Step 2, the selected UAV head h q computes the utility of all possible positions in the strategy space and finds the optimal position deployment with computational complexity OðC2Þ, where C2 is constant affected by the number of available positions in the UAV head's strategy space and the Equation ( 14).…”
Section: Algorithm Complexity Analysismentioning
confidence: 99%
“…Zhang et al 36 minimize the response latency of UAVs in MEC‐enabled UAV swarm networks by jointly optimizing communication and computation resources. Chen et al 37 investigated the joint optimization of scheduling, channel selection, and computation offloading in MEC‐enabled multi UAV swarm and ultimately optimized the relative latency of the networks. However, it ignored UAVs' maneuverability and intra‐coalition interference.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It optimized UAV under several constraints but with ideal assumptions which are not practical. In [32], the authors suggested MEC as a UAV network where coalition leaders serve as servers to aid members with data computation. They looked into relative delay optimization in MEC-assisted UAV swarms.…”
Section: Non Ai-based Solutionsmentioning
confidence: 99%
“…Unsupervised Learning [71] V2X, 6G, IoV [101] Vehicular ad hoc network [107] UAV Trajectory [73] Video+dataset [74] Maximizing the sum mean [121] Optimal path [113] UAV+Disaster NOMA [122] Beamforming & Beamsteering CH optimization+UAV [109] Microwave Power Transfer [123] UAV+Disaster & Resource allocation "CH" Supervised Learning [14] UAV+NOMA [26] UAV Trajectory [80] IRS with MIMO CH [124] UAV Trajectory [72] UAV in 6G [70] UAV Design [28] UAV Energy constrains [32] Mobile edge computing [90] Access to the cloud computing [110] Multiple UAVs [74] Maximizing the sum mean [89] Mobile edge computingDesign UAV [124] UAV Optimize the energy efficiency [30] Mobile edge computing…”
Section: Ai-uav Assisted Solutionsmentioning
confidence: 99%